Clinical Outcomes of Exercise Rehabilitation for Degenerative Tibial Meniscal Tears: A Systematic Review and Meta-Analysis of Randomized Controlled Trials [Response to Letter] - Mao S; Xiao K; Xu H; Wang Y; Guo X (Journal of Pain Research)
Sujie Mao,1 Kaiwen Xiao,2 Hong Xu,3 YanAn Wang,4 Xiujin Guo2 1Graduate Department, Harbin Sport University, Harbin, Heilongjiang, People’s Republic of China; 2Discipline Development Office, Nanjing Sport Institute, Nanjing, Jiangsu, People’s Republic of China; 3College of Sports and Health, Sangmyung University, South Korea; 4Academic Affairs Office, Jiangsu Police College, Nanjing, Jiangsu, People’s Republic of ChinaCorrespondence: Xiujin Guo, Nanjing Sport Institute, No. 8, Linggu Temple, XuanWu District, Nanjing, Jiangsu, People’s Republic of China, Email ntxiujin@163.com